CUSTOMER VALUE IN INDUSTRIAL MARKETS: IMPLICATIONS FOR SEGMENTATION AND PRICING - Luong, Dang (My University, 2025)
Industrial firms invest heavily in creating customer value through reliability, service, and technical expertise, yet struggle to capture this value through pricing. Despite sophisticated understanding of what customers value, pricing practices often remain anchored in cost-plus methodologies, creating a persistent value-price gap. This research investigates how conceptions of value shape segmentation and inform value-based pricing strategies in industrial markets. Through qualitative analysis of managerial interviews at Company A, this study employs an approach involving semi-structured interviews with managers across sales, product management, and pricing functions. Systematic coding revealed four aggregate dimensions explaining the value-price gap. First, industrial value comprises a multidimensional architecture spanning operational risk mitigation, service continuity, lifecycle economic value, knowledge co-creation, and symbolic value each activated contextually rather than universally. Second, value-contingent segmentation reveals that organizational decision structures and stakeholder configurations better predict value priorities than firmographic characteristics alone. Third, value translation mechanisms including pricing corridors and specification influence partially incorporate value into pricing but remain tactical adaptations rather than systematic frameworks. Fourth, systemic capability deficits spanning value quantification tools, information infrastructure, sales competencies, and organizational alignment prevent value understanding from translating into value capture. The study introduces value-price decoupling, demonstrating that value understanding and value capture represent distinct organizational capabilities requiring different resources. It reveals capability interdependence where deficits in any domain constrain effectiveness in others, requiring coordinated transformation rather than sequential improvements. Managerial implications emphasize that value-based pricing transformation requires multi-year organizational change involving systematic value quantification tools, enhanced information infrastructure, transformed sales capabilities, refined segmentation approaches, and organizational alignment across compensation, governance, and culture. The research provides a practical implication for industrial firms seeking to systematically capture value through pricing.
Keywords: Pricing, Segmentation, Value, Value-based Pricing, Value-based Segmentation, Industrial Pricing